2005
DOI: 10.1002/pros.20172
|View full text |Cite
|
Sign up to set email alerts
|

Induction of AP-1 activity by androgen activation of the androgen receptor in LNCaP human prostate carcinoma cells

Abstract: Activation of androgen receptor by androgen induces changes in AP-1 activity and AP-1 factor DNA-binding that may contribute significantly to androgen-induced changes in prostate cancer cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…As is the case for other nuclear hormone receptors, Fos and Jun regulate the transcriptional activity of the androgen receptor (30,31,47), which may provide a mechanism by which they promote prostate tumorigenesis. Notably, previous studies have shown that Fos and Jun protein expression is up-regulated in hormone-refractory prostate cancer (28,29). Although the TMAs used in the current study do not directly address the relationship of Fos and Jun expression to androgen independence, most of the metastases in the progression TMA were from hormone-refractory patients (34); moreover, we also found that Fos and Jun were clearly elevated in androgen-independent tumors in our mouse model.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As is the case for other nuclear hormone receptors, Fos and Jun regulate the transcriptional activity of the androgen receptor (30,31,47), which may provide a mechanism by which they promote prostate tumorigenesis. Notably, previous studies have shown that Fos and Jun protein expression is up-regulated in hormone-refractory prostate cancer (28,29). Although the TMAs used in the current study do not directly address the relationship of Fos and Jun expression to androgen independence, most of the metastases in the progression TMA were from hormone-refractory patients (34); moreover, we also found that Fos and Jun were clearly elevated in androgen-independent tumors in our mouse model.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, previous studies have reported that Fos and Jun proteins are up-regulated in human prostate cancer, particularly in hormone-refractory disease (28,29), where they can modulate the transcriptional activity of the androgen receptor (30)(31)(32). However, some studies have found that the levels of Fos and/or Jun RNA may be reduced in human prostate tumors (e.g., ref.…”
Section: Resultsmentioning
confidence: 99%
“…JunD plays important regulatory roles in both androgen-dependent and androgen-independent prostate cancer cells by functioning as a co-activator for the androgen receptor to mediate androgen-induced oxidative stress in LNCaP cells (51,74) or by interacting with the NFB pathway to induce IL-6, an important mediator of metastatic, hormone-refractory prostate cancer (75). On the other hand, Church et al (50) reported that cell growth inhibition in LNCaP cells after treatment with androgens resulted in a concomitant increase in JunD expression. This suggests that AP-1 regulation of cell proliferation depends on the cellular "context" and on the combination of available contributing factors and active pathways in each target tissue.…”
Section: Figure 6 Tgf-␤1 Did Not Induce Jund or Sapk/jnk Phosphorylamentioning
confidence: 99%
“…In a recent report, JunB was shown to play an important role in maintaining cell senescence that blocks malignant prostate cell transformations (48) and has been shown to be a potent activator of KAI1 (49). Jun proteins by themselves or in combination with members of the Fos proteins have also been implicated in the actions of androgens (50,51), atmospheric pollutants (52), growth factors (53), phytochemicals (54 -56), peroxides (57), isothiocyanates (58), glycoproteins (59), and, most recently, proteasome inhibitors (60). AP-1 proteins form multiple homo-and heterodimers, and the composition of these dimers may dictate expression of specific genes involved in specific biological responses.…”
mentioning
confidence: 99%
“…Activated receptors bind directly to specific progesterone response elements (PREs) and PRE-like sequences in the promoter regions of such target genes as c-myc [9], fatty acid synthetase [10], and MMTV [11]. Treatment with progestin also results in an upregulation of regulatory molecules without classical PREs in their proximal promoter regions, such as Epidermal Growth Factor Receptor [12,13], cfos [14,15], and cyclin D1 [16,17]. Without canonical PREs, PR regulation of these genes can occur through indirect DNA-binding mechanisms, as in the example of PR binding to Specificity protein 1 to promote p21 transcription in the presence of progestin [18].…”
Section: Classical Actions Of Prsmentioning
confidence: 99%